What (why) does factor influence fraud tendency in public sector? - Dewi Indriasih; Dien Noviany Rahmatika; Aminul Fajri (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2020)
The purpose of this study is to prove that internal control, compliance in accounting rules, and unethical behavior are factors that influence fraud tendency. The city that has never been awarded the unqualified since 2013-2018 taken as a sample and used multiple linear regression in the data processing. The results show that internal control, compliance, and unethical behavior have a significant effect on fraud tendency. Internal control and compliance with positive influences in reducing fraud tendency; and unethical behavior with negative impacts. This finding also proves that there is no systematic intention in fraud.